A ladle heat loss model for daily production. (2017) - Rahmani, Keyvan; Thomson, Vincent
Production events and uncertainties impact ladle processing times, which in turn affect the steel temperature at the tundish. Deviations from the desired steel temperature in the tundish can result in production stoppage either due to premature solidification or due to liquid steel leakage at the caster. These stoppages are extremely costly and must be avoided by any means. Using a good method for estimation of heat losses that is linked to production parameters is very useful to reduce the risk of incorrect steel temperature. Most of the literature to date on computing the ladle heat loss is concerned with analytical and numerical solutions that are interesting academically or with regards to ladle design. This paper however is concerned with building a gross heat loss estimation model for a ladle in daily operation. It studies the important parameters that affect final steel temperature and uses actual production data to validate the analyses and conclusions. A rule of thumb for the cooling rate of steel in a ladle is developed with an average value of 0.55 to 1.40°C/min. [Received 25 December 2015; Accepted 22 February 2017]